2017
DOI: 10.18203/2320-6012.ijrms20170640
|View full text |Cite
|
Sign up to set email alerts
|

The effect of general anaesthesia versus conscious sedation in dosimetric distribution of intracavitary radiotherapy in cervical cancer patients

Abstract: Background: Majority of Indian patients presents in locally advanced stage and most of them treated by combination of external teletherapy and intracavitary brachytherapy (ICRT). Because of deficient infrastructure, the waiting period is generally long at existing caner canters. Hence ICRT may be done in conscious sedation to treat more patients by avoiding time consuming general anaesthesia. The aim of this study is to know the effect of general anaesthesia vs. conscious sedation in dosimetric distribution in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…This could be due to the better adequate vaginal packing as a result of better muscle relaxation under GA. A study of comparison of HDR-ICBT dosimetry with and without anaesthesia done by Sharma et al showed that mean dose to the bladder reference point was 5.03 Gy (71.85% of point A dose) in the anaesthesia group compared to 4.90 Gy (70% of point A dose) in patients without anaesthesia (p value 0.6) and mean dose to the rectal point was significantly higher in anaesthesia group compared to patients without anaesthesia (5.09 Gy v/s 4.49 Gy, p value 0.01) [8]. In a similar study done by Rathore et al, mean dose to the bladder was in the range of 17.7-69.3% and 15.54-74.24% in anaesthesia and conscious sedation (CS) groups respectively, mean dose to the rectum was 32.5-77.73% and 21.07-79.16% in the anaesthesia and CS groups respectively, and they concluded that dosimetric parameters in both the groups were similar and did not depend on the type of anaesthesia [9]. Both these studies used 2D conventional planning for dosimetric evaluation; we on the contrary used CT-based volumetric planning for dosimetric evaluation of the OARs.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to the better adequate vaginal packing as a result of better muscle relaxation under GA. A study of comparison of HDR-ICBT dosimetry with and without anaesthesia done by Sharma et al showed that mean dose to the bladder reference point was 5.03 Gy (71.85% of point A dose) in the anaesthesia group compared to 4.90 Gy (70% of point A dose) in patients without anaesthesia (p value 0.6) and mean dose to the rectal point was significantly higher in anaesthesia group compared to patients without anaesthesia (5.09 Gy v/s 4.49 Gy, p value 0.01) [8]. In a similar study done by Rathore et al, mean dose to the bladder was in the range of 17.7-69.3% and 15.54-74.24% in anaesthesia and conscious sedation (CS) groups respectively, mean dose to the rectum was 32.5-77.73% and 21.07-79.16% in the anaesthesia and CS groups respectively, and they concluded that dosimetric parameters in both the groups were similar and did not depend on the type of anaesthesia [9]. Both these studies used 2D conventional planning for dosimetric evaluation; we on the contrary used CT-based volumetric planning for dosimetric evaluation of the OARs.…”
Section: Discussionmentioning
confidence: 99%